Context and Implications Document for: Who you know, what you know and knowing the ropes: a review of evidence about access to higher education institutions in England. Issue 1 (2nd March 2015) - Whitty, Geoff; Hayton, Annette; Tang, Sarah
<x xml:space="preserve">Abstract</x> This guide accompanies the following article: G. Whitty, A. Hayton and S. Tang. Who you know, what you know and knowing the ropes: a review of evidence about access to higher education institutions in England. Review of Education, DOI:10.1002/rev3.3038